Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b) /x-1/=0
x-1=0
x=1
Vậy x=1
c) 2./x-3/=6
|x-3|=3
\(\Rightarrow\orbr{\begin{cases}x-3=3\\x-3=-3\end{cases}}\)\(\Rightarrow\orbr{\begin{cases}x=6\\x=0\end{cases}}\)
30 - (x + 2) = 14
(x + 2) = 30 - 14
x + 2 = 16
x = 16 - 2
x = 14
2018 x ( 2017 - x ) = 0
(2017 - x) = 0 : 2018
2017 - x = 0
x = 0 + 2017
x = 2017
720 : { 41 - ( 2x - 5 ) } = 40
{ 41 - ( 2x - 5 ) } = 720 : 40
{ 41 - ( 2x - 5 ) } = 18
( 2x - 5 ) = 18 + 41
( 2x - 5 ) = 59
2x = 59 + 5
2x = 64
x = 64 : 2
x = 32
(x + 1) ( x+2 ) (x+3) + ....+ ( x+100 ) = 5750
(x + x + x + ... + x) + (1 + 2 + 3 + ... + 100) = 5750
(x .100) + (1+100) . 100 : 2 = 5750
(x.100) + 5050 = 5750
x.100 = 5750 - 5050
x . 100 = 700
x = 700 : 100
x =7
a. 30 - (x + 2) = 14
x + 2 = 30 - 14
x = 16 - 2
x = 14
b. 2018 . (2017 - x) = 0
2017 - x = 0 : 2018
x = 2017 - 0
x = 2017
c. 720 : [41 - (2x - 5)] = 40
41 - (2x - 5) = 720 : 40
2x - 5 = 41 - 18
2x = 23 + 5
x = 28 : 2
x = 14
d. (x + 1) (x + 2) (x + 3) + ... + (x + 100) = 5750
(x + x +...+ x + x) (1 + 2 + 3 + ... + 100) = 5750
100x + [(1 + 100) . 100 : 2 ] = 5750
100x + 5050 = 5750
100x = 5750 - 5050
x = 700 : 100
x = 7
x(x+1)+(x+2)+(x+3)+...+(x+100)=5750
=> (x+x+x+x+...+x)+(1+2+3+...+100)=5750
=> 101x+5050=5750
101x = 5750-5050
101x = 700
x = 700 : 101
x = 700/101
(x + 1) + (x + 2) + (x + 3) + ... + (x + 100) = 5750
=> x + 1 + x + 2 + x + 3 + ... + x + 100 = 5750
=> (x + x + x + .... + x) + (1 + 2 + 3 + 4 + ... + 100) = 5750 (100 số hạng x)
=> 100x + \(\left[\left(100-1\right):1+1\right].\left(\frac{100+1}{2}\right)\) = 5750
=> 100x + \(100.\frac{101}{2}\)= 5750
=> 100x + 5050 = 5750
=> 100x = 5750 - 5050
=> 100x = 700
=> x = 700 : 100
=> x = 7
Ta có:
(x + 1) + (x + 2) + ... +(x + 100) = 5750
100x + 1 +2 + 3 + 4 + 5 +... + 100= 5750
100x + \(\frac{1+100}{2}\) = 5750
100x + 1+ 100 = 11500
100x = 11399
x = 113,99
(x+1)+(x+2)+(x+3)+...+(x+100)=5750
=>(x+x+x+...+x)+(1+2+3+4+....100)=5750
100 số 100 số
=>100x+(100+1)*100:2=5750
=>100x+5050
=>100x=5750-5050
=>100x=700
=>x=700:100
=>x=7
Vậy x=7
(x + 1) + (x + 2) + (x + 3) + ... + (x + 100) = 5750
(x + x + x + ... + x) + (1 + 2 + 3 + .. + 100) = 5750
100x + 5050 = 5750
100x = 5750 - 5050
100x = 700
x = 7
(x + 1) + (x + 2) + (x + 3) + ... + (x + 100) = 5750
(x + x + x + ... + x) + (1 + 2 + 3 + ... + 100) = 5750
100 số x 100 số
100x + (1 + 100) × 100 : 2 = 5750
100x + 101 × 50 = 5750
100x + 5050 = 5750
100x = 5750 - 5050
100x = 700
x = 700 : 100
x = 7
Vậy x = 7
(x + 1) + (x + 2) + (x + 3) + ... + (x + 100) = 5750
(x + x + x + ... + x) + (1 + 2 + 3 + ... + 100) = 5750
100 số x 100 số
100x + (1 + 100) × 100 : 2 = 5750
100x + 101 × 50 = 5750
100x + 5050 = 5750
100x = 5750 - 5050
100x = 700
x = 700 : 100
x = 7
Vậy x = 7
=> x + 1 + x + 2 + x + 3 +...+ x + 100 = 5750
=> (1 + 2 + 3 + ... + 100) + ( x + x + x + ... + x) = 5750
=> 100x + 5050 = 5750
=> 100x = 700
=> x= 7
Vậy x=7
phí giấy thế